Classical R-Operators and Integrable Generalizations of Thirring Equations - Skrypnyk, T.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We construct different integrable generalizations of the massive Thirring equations corresponding loop algebras gσ in different gradings and associated ''triangular'' R-operators. We consider the most interesting cases connected with the Coxeter automorphisms, second order automorphisms and with ''Kostant-Adler-Symes'' R-operators. We recover a known matrix generalization of the complex Thirring equations as a partial case of our construction.